STREAM DlVERSION IN THE EAST AFRICAN RIFT VALLEY - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
High above the Kerio Valley on the western escarpment of Kenya's Rift Valley live the Marakwet. They grow cereals, principally finger millet and sorghum, and combine this with pastoralism, the women cultivating the crops and the men herding the...